Gambaran Pemasaran Hasil Karya Busana Jahitan Warga Belajar di PKBM Anarvani - Novia Dellima; Syafruddin Wahid (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is based on the sewing activity at PKBM Anarvani which is taught directly by the instructor. By the existence of the work of the sewing clothes of the learners, it creates the cooperation between some fashion Muslim shops with PKBM Anarvani. So that, there must be the order of fashion Muslim to the PKBM Anarvani. The type of fashion muslim order which is famous in community and documented in PKBM Anarvani are the works that showed by the cooperation of PKBM Anarvani, then the marketing is done through social media like facebook, instagram, whatsapp, or even others social media. The type of research is quantitative research. The population of the research is the participants of the training for 20 people. The sampling technique in this research is purposive random sampling. The data collection is using questioner and its data analysis formulated by the percentage. The result of the research shows: the planning of the sewing work’s marketing is in good category, the determination of label’s product and price are in good category, the promotion activity which is done in the sewing work’s marketing is in good category, the distribution in the sewing work’s marketing is in good category.Keywords: Marketing, Sewing Clothing, Learning Citizens, PKBM